Erythropoietin attenuates propofol-induced hippocampal neuronal cell injury in developing rats by inhibiting toll-like receptor 4 expression. (18th January 2020) - Zhang, Chun-yan; Du, Juan; Zhang, Rui; Jin, Jin; Qiao, Le-yan
Highlights: Erythropoietin can attenuate propofol-induced hippocampal neuronal cell injury in developing rats. Erythropoietin can attenuate hippocampal neuronal cell injury via inhibiting TLR4 expression. Erythropoietin up-regulated the expression of Ki-67, PCNA, Bcl-2, NGF, BDNF and NT-3 in developing rats. Erythropoietin decreased the expression of Bax, Caspase-3, TLR4 and p65. Abstract: Background: This study was to investigate the neuroprotective effect of erythropoietin (EPO) on hippocampal neuronal cell injury in developing rats. Methods: The hippocampal neurons cells were obtained from SD rats aged 10 days and divided into control, propofol, EPO, and propofol + erythropoietin (E + P) groups. Cell proliferation and apoptosis were measured by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), Ki-67 immunofluorescence, and flow cytometry, respectively. The levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, IL-4 and IL-10 were detected by enzyme-linked immunosorbent assay (ELISA). Cellular immunohistochemistry was utilized to detect the expression of proliferating cell nuclear antigen (PCNA), nerve growth factor (NGF), brain derived neurotrophic factor (BDNF), and neurotrophin-3 (NT-3). Quantitative real time polymerase chain reaction (qRT-PCR) and western blot were used to detect the expression of Bax, Bcl-2, Caspase-3, toll-like receptor 4 (TLR4) and p65. Furthermore, TLR4 antagonist (TAK-242) and activator (LPS) were used to study the relationship between EPO and TLR4. Results: Propofol treatment caused morphological and structural damage of hippocampal neurons. However, EPO significantly improved this damage, enhanced cell proliferation, decreased apoptosis and pro-inflammatory factor content, up-regulated the expression of Ki-67, PCNA, Bcl-2, NGF, BDNF and NT-3, as well as decreased the expression of Bax, Caspase-3, TLR4 and p65 (p < 0.05). After TAK-242 or LPS treatment, it showed similar results in propofol + TAK-242 (T + P) group and E + P group. Conclusion: Erythropoietin could attenuate propofol-induced hippocampal neuronal cell injury in developing rats, which may be related to inhibit TLR4 expression.